Development and validation of standard and real patient gallstone library using Fourier transform infra-red spectroscopy. - Jafri, Lena; Abid, Muhammad Abbas; Asif, Humera; Hashmi, Bilal; Majid, Hafsa; Ghani, Farooq; Ahmed, Sibtain; Siddiqui, Imran; Khan, Aysha Habib (BMC Gastroenterology, 2022)
Background: Analysis of the constituents of gallstones using various spectroscopic techniques assists in identification of the pathogenesis of gallstones. In the current study, using Fourier Transform Infra-Red (FTIR) Spectroscopy, a Gallstone Standard Library (GSL) and a Gallstone Real Patients' Library (GRPL) were developed and validated for gallstone composition analysis.Methods: The study was conducted at the Department of Pathology & Laboratory Medicine, Aga Khan University, Pakistan. Pure standards (cholesterol, calcium carbonate, bilirubin and bile salts) and gallstone specimens were analyzed using FTIR Nicolet iS-5 Spectrometer from Thermo Fisher Scientific, USA. Thermo Scientific™ QCheck™ algorithm, embedded within the OMNIC™ software, was used to identify the unique spectral fingerprint of the patient samples to match with known, standard material. Matching of > 75% was considered acceptable. Validation for accuracy of the library was performed for twenty analyzed gallstones at an international reference lab.Results: Concerted search analysis was performed against the developed GSL consisting of 71 "pure component" spectrum divided into 5 types to generate the library. For the Gallstone Real Patient Library (GRPL), 117 patient samples were analyzed. Ninety-eight gall stones (83.8%) out of 117 stones matched with the developed GSL. Majority stones were mixed stones (95.92%), with cholesterol being the primary component (91.83%). Results of the developed library were 100% in agreement with the reports received from the external reference lab.Conclusions: The library developed displayed good consistency and can be used for detection of gallstone composition in Pakistan and replace the traditional labor- and time-intensive chemical method of gallstone analysis.